Metal Complex-Peptide Conjugates: How to Modulate Bioactivity of Metal-Containing Compounds by the Attachment to Peptides - Neundorf, Ines (Current Medicinal Chemistry, 2017)
During the last years, the interest in combining the features of metal-containing molecules with biomolecules, particularly peptides, has been increased. Large series of new innovative organometallic compounds, as well as potent coordination complexes have been designed and, especially in medicinal chemistry, the library of bioactive compounds was excessively expanded by the introduction of metal complexes. The research foci are divers and not limited to e.g. the development of therapeutics with anti-proliferative or antibacterial activity, or the design of novel biosensors useful for pharmaceutical applications. By introduction of a metal centre, new attributes might be added that could help to overcome the problems of difficult to treat diseases, as well as to combat issues with arising drug resistances. However, the application of a number of very potent metal complexes is restricted owing to their poor water-solubility, air-stability and only poor uptake when in contact with cells. In this context, one possibility to optimize promising lead structures is to couple them to bioactive peptides. Within this review, an overview on metal complex-peptide conjugates used for drug design and future pharmaceutical application is presented.
Keywords: antimicrobial peptides